The History of Passover: Changes in the Religion and Cult of the Judeans in 7th-5th Centuries BCE - Niesiołowski-Spanò, Łukasz (Revue biblique, 2020)
Despite the fact that Passover constitutes one of the most important Jewish feasts, its origins still remain somehow obscure. Biblical references indicate two incompatible traditions about the original character of Passover: a domestic ritual of common Israelites, or a central cultic ritual in the Jerusalem sanctuary. The article aims to present the hypothesis that the central royal sacrifice in Jerusalem in the late 7th century BCE evolved into the domestic feast of "common Israelites" during the Babylonian Exile. This proposal finds support in John Van Seters’ reconstruction of the process of the composition of the Exodus-narratives during the Exile. The next changes in Passover took place in the mid-5th century BCE, linked to the process of establishing the new cultic calendar. A domestic-like feast was anchored to the fixed days of the month, and incorporated into the pilgrimage to the central sanctuary. This process is well illustrated by the testimonies from Elephantine, in the 5th century BCE. The article concludes by pointing out possible neglected political contexts of the religious reform in 5th century Jehud.